People priorities and perceptions: towards conservation partnership in Mamberamo - Boissiere, M.; Liswanti, N.; Padmanaba, M.; Sheil, Douglas (Center for International Forestry Research, 2007)
This report refers to the follow-up activities in Mamberamo developed by CIFOR and CI in 2006. The new activities included additional socio-economic surveys in three villages. The accuracy of the participatory maps of the natural resources and important landscape features were improved using GPS ground checks. Participatory maps of territorial land claims and land use by clans were also drafted. Additional information was then collected on local biodiversity monitoring and control of the land and resources. The results show that local communities with village territories of between 1000 and 1700 km2 per village which they regularly patrol, have a strong awareness of the threats to their wild resources, and equally the need to maintain the watershed’s services.